DETERMINAN KEJADIAN GANGGUAN SISTEM PERNAPASAN PADA PENGRAJIN DUPA DI PABRIK DUPA BUNGA WANGI SELEMADEG, TABANAN - Tresnawulandari, Kadek Titin; Wirawan, I Md. Ady (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024, 2025)
Occupational Diseases are diseases caused by unsafe action and unsafe condition. Based on BPJS Employment data, there were 1,123 cases of work-related diseases in Indonesia, while in mid-2022 there were 753 cases of work-related diseases in Indonesia. The sawdust used in the incense industry produces dust which causes respiratory problems. The purpose of this study was to determine the incidence of respiratory system disorders and the factors that influence respiratory system disorders in incense craftsmen at the Bunga Wangi Incense Factory, Selemadeg, Tabanan. This research is quantitative analytic with cross sectional design. The sample is 23 people. Data collection was carried out through questionnaires and spirometry measurements which were then analyzed using the Mann-Whitney U Test and the Binomial Logistic Regression Test. The results of this study showed that 91.3% of respondents experienced complaints of respiratory system disorders and 73.9% of respondents experienced impaired lung function. There was a significant relationship between medical history (p=0.015), smoking habits (p=0.009), behavior in using PPE (p=0.041), and perceptions of the work environment (p=0.012) to complaints of respiratory system disorders in incense makers. There was a significant relationship between history of disease (p=0.035) and lung function capacity. The management should make SOPs, provide PPE for workers, and provide air conditioning in the workspace. Workers who have impaired lung function should use masks properly when working. Keywords: Respiratory System Disorders, Wood Dust, Incense Factory, Lung Function Capacity